LEGAL REFORM DALAM PENJATUHAN SANKSI TERHADAP ANAK PELAKU KEJAHATAN - Ni Nyoman Juwita Arsawati; Anak Agung Ayu Ngurah Tini Rusmini Gorda (Jurnal Analisis Hukum, 2018)
The child needs to be protected both physically and spiritually, especially when the child is a criminal. Children to be accountable for their actions, not separated from the imposition of criminal punishment of imprisonment. The imposition of imprisonment on children is irrelevant compared to the crime rate, and it seems that imprisonment does not deter the perpetrator. It can be attributed to a child's crime similar to that of an adult whether in quantity or quality. This situation certainly raises issues both philosophically, juridically and sociologically. It is deemed necessary to reform the criminal law in the face of children as perpetrators of crime, deprivation of liberty by placing children in prison, unable to provide protection from the deprivation of the rights of children as opposed to the values of Pancasila as stipulated in the second precept " humanitarian "so it is necessary to replace it with alternative criminal (alternative sanction) one of them in the form of criminal supervision as regulated in Article 71 of Law No.11 Year 2012 About Child Criminal Justice System. Characteristics of the imposition of criminal surveillance of the child, perpetrators are still given the opportunity to improve themselves, and supervision is made in accordance with the personal needs of children who promote human coaching, by upholding the dignity of children based on the principle of "humanity". This is certainly in accordance with the idea or ideals of law and the reality of society that is upholding a democratic, social and humane life, which became the basic color of Indonesian law based on Pancasila.Keywords :Legal reform, children of perpetrators of crime, imposition of sanctions